Efficiency of Learning Methods in Building the Character of Madrasah Aliyah Students - Natalia Rumanti Hartono; Suhari Muharam; Dahlan Abdullah; Wily Mohammad; Abdul Wahab (Yayasan Adra Karima Hubbi, 2023)
Background. One of the common causes is attitude, a complex problem experienced by students at the Aliyah level causing less serious learning. Behavior will have a special impact on the social aspects of life. So it takes more effort for a teacher to prevent and anticipate unwanted things from happening. Purpose. The purpose of this study, to how the application of overcoming the attitude of Madrasah Aliyah students in interacting both with each other and with other educators, through the Efficiency of Learning Methods. Method. This research uses quantitative methods by using surveys and in-depth interviews with educators. The results of this study are educators looking for a middle point on how to build the character of Aliyah students through the Efficiency of Learning Methods. Results The conclusion of this research is that educators can take advantage of providing material that is already in the syllabus for learning to make student character can be formed. Conclusion. Therefore, the limitation of this study is that researchers cannot present valid behavioral data for each Aliyah student. It is hoped that future researchers can present an in-depth look at the behavioral problems that exist in Aliyah students.